2021
DOI: 10.2166/aqua.2021.043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical fertilizers on arsenic mobilization in the alluvial Bengal delta plain: a critical review

Abstract: Arsenic contamination of alluvial aquifers of the Bengal delta plain causes a serious threat to human health for over 75 million people. The study aimed to explore the impacts of chemical fertilizer on arsenic mobilization in the sedimentary deposition of the alluvial Bengal delta plain. It selected ten comparatively higher affected Districts and the least affected two Divisions as a referral study site. The countrywide pooled concentration of arsenic in groundwater was 109.75 μg/L (52.59, 166.91) at a 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 101 publications
(118 reference statements)
1
15
0
Order By: Relevance
“…Currently, arsenic is present at a very high level (>50 μg/L) in at least 30% of the tube wells used to provide drinking water and approximately 50 million people use arsenic-contaminated water for their daily activities [ 23 , 24 ]. One of the major contributors to arsenic mobilization in groundwater is phosphate (PO 4 ) rich fertilizer leaching [ 25 ]. Therefore, in addition to contaminated drinking water, Bangladeshis also face the risk of arsenic exposure through the consumption of fish raised in aquaculture ponds and rice irrigated by arsenic-polluted water [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, arsenic is present at a very high level (>50 μg/L) in at least 30% of the tube wells used to provide drinking water and approximately 50 million people use arsenic-contaminated water for their daily activities [ 23 , 24 ]. One of the major contributors to arsenic mobilization in groundwater is phosphate (PO 4 ) rich fertilizer leaching [ 25 ]. Therefore, in addition to contaminated drinking water, Bangladeshis also face the risk of arsenic exposure through the consumption of fish raised in aquaculture ponds and rice irrigated by arsenic-polluted water [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2015) [25] identified the major sources of As pollution and NABARD (2016) [26] showed the usage of chemical fertilizer increased dramatically during the time period from 1950 to 2016 in north 24 parganas district. Moreover, Islam and Mostafa (2021) [27] described the higher contribution of As from chemical fertilizer in the Bengal delta plain. The present study showed that 14 sampling point exceed the acceptable limit (according to BIS (2012) [21] 0.05 mg/L, Table 3) of As regarding drinking water purpose.…”
Section: Resultsmentioning
confidence: 99%
“…The highest concentration of arsenic detected in the shallow tubewell water was 470 µgm/L and a previous study conducted by the experts of the Bangladesh Council for Scientific and Industrial Research (BCSIR) have found also the highest concentration of 1400 µgm/L in the same types of tube-well water of Pabna district (New Nation Report, 1996). In Bangladesh, two predominant hypotheses stating the mobilization of arsenic in groundwater are pyrite oxidation and the reduction of metal oxy-hydroxide (Islam and Mostafa, 2021f).…”
Section: Fig 3: Distribution Of Arsenic In Groundwater Of Bangladeshmentioning
confidence: 99%